ACCESSIBILITY AND USABILITY OF GENERATIVE AI FOR TEACHING AMONG SECONDARY SCHOOL CHEMISTRY TEACHERS IN ILORIN METROPOLIS, KWARA STATE - IBRAHIM, Abdulmuhsin; OYEYEMI, Waheed Tunde; AHMED, Adedolapo Abdulahi (Jurnal Saintifik (Multi Science Journal), 2025)
This study examines how easily secondary school chemistry teachers in Ilorin Metropolis, Kwara State, can access and use generative AI tools. Assessing instructors' knowledge of generative artificial intelligence (AI), the accessibility of these resources, and their usefulness in chemistry instruction was its primary goal. Data were gathered from 333 chemistry teachers in the city's different local administrations using a descriptive survey design. The results showed significant awareness gaps, with many teachers not knowing about the benefits and pedagogical potential of generative artificial intelligence. Furthermore, it was discovered that these programs had restricted accessibility; the only one with moderate availability was ChatGPT. The survey also found that using the majority of AI tools in classroom settings can be difficult. The study suggests creating focused professional development programs to increase teachers' comprehension of generative artificial intelligence in light of these findings. It also recommends expanding access to these tools by giving schools the resources and infrastructure they require. Furthermore, more approachable, teacher-focused AI systems that are tailored to the unique requirements of chemistry education must be developed. These steps are intended to help educators better incorporate AI into their lesson plans and improve students' understanding of difficult chemistry concepts.